Tricoderma harzianum T32 growth and antagonistic performance against Ganoderma boninense of different culture media. - Laila Naher; Seri Intan Mokhtar; Noorhazira Sidek (2015)
The genus of Trichoderma are ubiquitous recommended as good biocontrol agent. The biocontrol activity depend on the medium. Thus, this study was conducted to observed the growth performance of Trichoderma harzianum strain T32 for physiological growth and biocontrol mode of action against Ganoderma boninense, (pathogen for palm and rubber trees) on different media of Potato dextrose agar (PDA), Potato Sucrose agar (PSA), and Malt extract agar (MEA). As for the physiological growth performance of the T32 on different media the greenish colour was observed in PDA/PSA media while in MEA the colour was yellowish green. The concentric ring structure was found in PSA, PDA, and MEA media. Antagonistic activity was higher in PDA media as Trichoderma harzianum T32 showed the highest 70% antagonistic activity against G. boninense. In conclusion, the resulting data showed that the morphological colour can be different based on medium as well as the biocontrol activity was differ based on medium.